The importance of politics in analyzing stock market reaction to U.S. companies´ misconducts: an event study - Paiva, Henrique José Gaspar (2021)
This paper addresses the noteworthy relevance of U.S. Politics in explaining the impact of corporate misconducts on stock returns. Using a database of regulatory violations in the U.S., the Event Study framework was employed to quantify, for each mis behavior, the resultant effect on the felonious firm’s stock. Those effects were then regressed on focal dummy variables, mirroring the acting political landscape. Ultimately, it is proven mis conducts happening under one party control of both Executive and Legislative branches tended to result in higher stock returns than if there is division of any sort. This research is among the first attempts to directly relate regulatory violations and Politics.